Insertion, elimination and isomerisation of olefins at alkylaluminium hydride: an experimental and theoretical study. Issue 34 (4th June 2015) - Weliange, Nandita M.; McGuinness, David S.; Gardiner, Michael G.; Patel, Jim
Abstract : Individual steps of the aluminium-mediated contrathermodynamic isomerisation of internal olefins to α-olefins are studied. Abstract : The insertion, elimination and isomerisation of octenes with di- n -octylaluminium hydride [HAl(Oct)2 ], tri- n -octylaluminium [Al(Oct)3 ] and sec -octylaluminium species have been studied as individual steps in a putative aluminium based contrathermodynamic olefin isomerisation process. While elimination of 1-octene from [Al(Oct)3 ] is energetically unfavourable, the process is driven by high temperature vacuum distillation, leading to very high selectivity to 1-octene (>97%). At high conversions the [HAl(Oct)2 ] so obtained exists predominately as hydride-bridged cyclic oligomers, whereas at low conversion the mixed alkyl/hydride-bridged dimer [(Oct)2 Al(μ-H)(μ-Oct)Al(Oct)2 ] is the major species. Di- n -octylaluminium hydride recovered after olefin elimination may be recycled and is active toward re-insertion of octenes. Internal octenes ( cis - and trans -2-, 3- and 4-octene) only partially insert however, and even after prolonged heating there is no significant secondary to primary alkyl isomerisation evident.